2019
DOI: 10.1016/j.mayocp.2019.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Herpetic Keratitis in Atopic Dermatitis

Abstract: 26-year-old man with a history of atopic dermatitis presented with redness, lacrimation, and photopsia in both eyes, especially the right eye (Figure A), for 1 month. Visual acuity was 20/20 in the right eye and 20/25 in the left eye. Slitlamp examination with fluorescein dye revealed conjunctival hyperemia and dendritic corneal epithelial ulcer with terminal bulbs, findings that are consistent with herpes simplex keratitis (Figure B). Dendritic corneal ulcer is the most common subtype of herpes simplex kerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Skin barriers deteriorate from atopy in patients with atopic dermatitis, and recurrent eczema occurs in sensitive areas such as the eyelid. 1 Even itching caused by secondary causes, such as a larva settling in the eye, can trigger an atopic dermatitis attack, as seen with our patient. 2 We wanted to share this case to emphasize the importance of mucosal examination in dermatologic diseases.…”
supporting
confidence: 55%
“…Skin barriers deteriorate from atopy in patients with atopic dermatitis, and recurrent eczema occurs in sensitive areas such as the eyelid. 1 Even itching caused by secondary causes, such as a larva settling in the eye, can trigger an atopic dermatitis attack, as seen with our patient. 2 We wanted to share this case to emphasize the importance of mucosal examination in dermatologic diseases.…”
supporting
confidence: 55%
“…This was demonstrated in an openlabel multicentre study with 158 patients where preservative-free tafluprost was better tolerated compared to latanoprost containing preservative solution [11]. It is important to note, however, that a study by Jess T Whitson et al [12] found no significant difference in tear break-up time and corneal staining among prostaglandins with different BAK concentrations which included bimatoprost (0.005% BAK), latanoprost (0.02% BAK), and travoprost (safZia) [12].…”
Section: Non-ocular Adverse Reactions Of Prostaglandinsmentioning
confidence: 97%
“…This was demonstrated in an openlabel multicentre study with 158 patients where preservative-free tafluprost was better tolerated compared to latanoprost containing preservative solution [11]. It is important to note, however, that a study by Jess T Whitson et al [12] found no significant difference in tear break-up time and corneal staining among prostaglandins with different BAK concentrations which included bimatoprost (0.005% BAK), latanoprost (0.02% BAK), and travoprost (safZia) [12].…”
Section: Non-ocular Adverse Reactions Of Prostaglandinsmentioning
confidence: 97%